Monetary and Macroprudential Policy Complementarities: Evidence from European Credit Registers - Carlo Altavilla; Luc Laeven; José-Luis Peydró (ZBW - Leibniz Information Centre for Economics, 2021)
We show strong complementarities between monetary and macroprudential policies in influencing credit. We exploit credit register data - crucially from multiple (European) countries and for both corporate and household credit - in conjunction with monetary policy surprises and indicators of macroprudential policy actions. Expansive monetary policy boosts lending more in accommodative macroprudential environments. This complementary effect of monetary and macroprudential policy is stronger for: (i) expansionary (as opposed to contractionary) monetary policy; (ii) riskier borrowers; (iii) less capitalized banks (especially when lending to riskier borrowers); (iv) consumer and corporate loans (rather than mortgages); and (v) more (ex-ante) productive firms (especially for less capitalized banks).
Keywords: G21; G28; G32; G51; E58; 330; credit registers; household loans; corporate loans; monetary policy; macroprudential policy